Environmental regulations, R&D intensity, and enterprise profit rate: Understanding firm performance in heavy pollution industries - Chen, Meilan; Shi, Victor; Wei, Xiaobo (Frontiers in Environmental Science, 2022)
With the worldwide green revolution, especially "pollution prevention and control" as one major strategy, environmental issues have received more and more attention. Environmental regulations, as an institutional norm, directly or indirectly regulate corporate behavior. Therefore, it is significant to examine the relationship between corporate performance and environmental regulations. In this paper, we conduct an empirical study on the relationships among environmental regulations, R&D intensity, and enterprise profit rate. Our data are from the 395 A-share companies in heavy pollution industries listed on the Shanghai and Shenzhen Stock Exchanges in China from 2008 to 2017. Our methodologies include Ordinary Least Squares mixed regression, quantile regression, and Generalized Method of Moments estimation. Our main research findings include the following. First, environmental regulation and R&D intensity both have a positive impact on corporate profit rate at the 1% significance level. Second, there are "threshold" effects on the promotion of corporate profit rate by environmental regulations and R&D intensity. Third, the product of environmental regulation and R&D intensity has a positive impact on corporate profit margin at the 1% significance level. Fourth, the impacts of environmental regulations and R&D intensity on corporate profit rate vary at different quantiles. Finally, R&D intensity is a partial mediation variable in the relationship between environmental regulations and enterprise profit rate. In terms of policy insights, our results suggest that the government formulate appropriate environmental regulations and enhance the support for enterprise R&D to stimulate technological innovation in the heavy pollution industries.